Seasonal Variability of Endoparasites in the excreta of Cattle Egret (Bubulcus ibis) from Punjab and Haryana States - Ishamjeet; Tejdeep Kaur Kler (Annals of Arid Zone, 2025)
The Cattle Egret (Bubulcus ibis) is a bio-control agent, found commonly associated with cattle and is known for controlling cattle parasites. It is also recognized as a beneficial bird in agriculture due to its habit of preying on agricultural pests. Present study was carried out to investigate the endoparasites and their seasonal dynamics in the fecal samples of Cattle Egret. Freshly excreted fecal samples of Cattle Egret from Punjab Agricultural University, Ludhiana, and from the villages of Ludhiana (Punjab) and Jind (Haryana) were collected from August 2022 to July 2023 to conduct the study. Examination of the samples were done by fecal floatation and sedimentation methods which shows 14.44% were positive for the presence of parasitic eggs. Positive samples were infected with four endoparasitic species, a nematode (Strongyloides avium 7.77%), two Trematode (Echinostoma sp. 3.88% and Nephrostomum sp. 0.55%) and Apicomplexa (Coccidian oocyst 2.22%). Prevalence of nematode was highest with 53.8%, followed by trematode with 30.77% and coccidia with 15.38%. Season wise the prevalence of endoparasites was calculated and analysed statistically which shows season significantly affect the endoparasitic prevalence in Cattle Egret (p<0.05), being highest in Monsoon (28.33%), followed by summer season (13.33%), and winter season (1.67%). These results showed that chances of tranmission of the parasites is more in monsoon season. During the field visits, we observe thirteen other avian species sharing feeding habitat with Cattle Egret at the selected locations which may lead to tramission of the parasites to other birds.